RETRACTED: Physcion 8‐O‐β‐Glucopyranoside Exerts Anti‐Tumor Activity Against Non‐Small Cell Lung Cancer by Targeting PPARγ. Issue 5 (25th November 2018) - Du, Youyi; Lv, Zhuqing; Sun, Debin; Li, Yuan; Sun, Lei; Zhou, Jiafeng
ABSTRACT: Lung cancer is one of the most common causes of cancer related mortality. The present study is designed to investigate whether a naturally occurring anthraquinone compound, physcion 8‐O‐β‐glucopyranoside (PG) could exert anti‐cancer activity against non‐small cell lung cancer (NSCLC). Cell viability was determined by Cell Counting Kit‐8 (CCK‐8) assay. Cell cycle distribution and cell apoptosis were determined by flow cytometry. Expressions of marker proteins were assessed by western blot analysis. To examine the role of PPARγ (peroxisome proliferator‐activated receptor γ) in PG‐induced apoptosis and cell cycle arrest, PPARγ was knockdown using siRNA. In addition, a xenograft model was established to investigate the effect of PG in vivo. The results showed that PG markedly induced cell cycle arrest and apoptosis in human NSCLC cell lines A549 and H358. The anti‐tumor effect of PG in NSCLC cells was mediated by upregulation of PPARγ. Besides, in NSCLC cell lines, the anti‐cancer activity of PG was also examined in the xenograft mice model, which showed that PG could significantly reduce tumor burden and activate apoptotic signaling. Our results demonstrated that PG can be regarded as a candidate chemotherapeutic agent for lung cancer. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc. Anat Rec, 302:785–793, 2019. © 2018 Wiley Periodicals, Inc.